Researching Photographic Participatory Inquiry in an E-Learning Environment - Grushka, Kathryn; Bellette, Aaron; Holbrook, Allyson (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2014)
This article focuses on the use of Photographic Participatory Inquiry (PPI) in researching the teaching and learning of photography in the e-learning environment. It is an arts-informed method drawing on digital tools to capture collective information as digital artefacts, which can then be accessed and harnessed to build critical and reflective photographic practices. The multimedia tools employed (for example GoPro video and screen capture) are critically discussed for their potential to contribute understanding of photographic artistic practice and the learning of a digital generation. The article may also provide critical insights and inform more nuanced methods for research and scholarship when wishing to investigate the personalized, participatory, and productive pedagogies of a networked learning society.